The expression in exponential form equivalent to the given expression (a)(a)(a)(a)(a)(a) is a⁶.
Exponentiation is a method of writing numbers in the powers form. It is generally useful for writing large numbers.
A number written in the exponent form means that the number is multiplied to itself many times as the number in the exponent.
A number aᵇ, read as a raise to b, is in the exponential form, where a is called the base and b is called the exponent. This means that a is multiplied to itself b times.
Here the given expression is (a)(a)(a)(a)(a)(a).
That is, the number 'a' is multiplied to itself 6 times.
So we should write an expression with base 'a' and exponent equals 6.
The expression is a⁶.
Hence, the required exponential form of the expression (a)(a)(a)(a)(a)(a) is a⁶.
To learn more about Exponents, click on the link given below:
#SPJ2
Answer:
a^-6
Step-by-step explanation:
I got it correct
yw
Answer:
y = 2/5x + 39/5
Step-by-step explanation:
point slope form is y = mx + b
so far we have y = 2/5x + b
m is slope which is given. We need to find b which is y-intercept.
They give us the point (-2,7). We can plug this into the equation to find b.
7 = 2/5(-2) + b
7 = -4/5 + b
b = 39/5
The equation now looks like y = 2/5x + 39/5
x2 – 10
x4 – 10x2 + 100
x4 + 10x2 + 100
C is the Correct Answer 100%.
Mark Brainiest Answer plz.
Answer:
The numbers in a table are often the x and y values that are true for the line, which means the x and y values correspond to the coordinates of points on the line.
Given that a line equation is y=m x+b, the x and y values are numbers that can be used to arrive at the unknowns, such as the slope(m) and the y-intercept(b).
with the help of two points/coordinates we could find the slope of a line and the 3rd coordinate could be used to find the y-intercept.
Answer: 220 miles
Step-by-step explanation:
Distance travelled is calculated as:
= Speed × Time
Based on the scenario on the question, the total distance, in miles, of Darius' trip will be:
= (60 × 2) + (50 × 2)
= 120 + 100
= 220 miles
Hello from MrBillDoesMath!
Answer:
y = x - 7
Discussion:
Let's step through the answers one-by-one:
y/6 = x => multiply both sides by 6
y = 6x
y = kx where k = 6
y/x = 1/2 => multiply both sides by x
y = (1/2) x
y = kx where k = 1/2
y = -0.5x
y = kx where k = -0.5
BUT y = x -7 cannot be written simply as y = kx because of the -7 term.
Thank you,
MrB
Answer:
C. y = x - 7
Step-by-step explanation: